Allocation concealment appraisal of clinical therapy trials using the extended Composite Quality Score (CQS-2)—An empirically based update - Mickenautsch, Steffen; Yengopal, Veerasamy (Frontiers in Medicine, 2023)
Objectives The objective of this study was to revise CQS-2/Criterion II concerning allocation concealment appraisal for prospective, controlled clinical therapy trials. Methods Meta-analyses of trials with inadequate allocation concealment were tested for in-between trial heterogeneity (I2 > 0) due to imbalances in baseline variables. Meta-analyses with positive test results were used as a basis to deduce criteria for adequate allocation concealment. The CQS-2/Criterion II was reformulated in line with the findings. Result One suitable meta-analysis was identified. Two forest plots with data from five and four trials with inadequate/unclear allocation concealment were selected for testing. In addition, a total of five trials with adequate allocation concealment were identified. The meta-analysis test results were positive, and keywords for the judgment of adequate allocation concealment were extracted verbatim from the text of the meta-analysis. The extracted keywords indicated “central allocation” as the main criterion for adequate allocation concealment. Criterion II of the CQS-2 was revised accordingly. Conclusion Criterion II of the CQS-2 trial appraisal tool was revised. The revised appraisal tool was specified as version CQS-2B.